On the state of harmonization of technical standards in the field of aluminum products with international and european standards - Pleshakov E. I.; Bohun L. I.; Shvachko S. G. (Металознавство та обробка металів, 2018)
The changes that are introduced into the designation of aluminum grades, foundry and deformable aluminum alloys are analyzed in accordance with the Law of Ukraine "On Standardization", which reorientes the national standardization system to European and international standards. The structure and content of existing national standards, including those harmonized with international and European standards, harmonization of existing standards, terms of their validity, prospects for application and development are characterized.